MEMBANGUN KERANGKA TEORITIS ILMU PEMASARAN (Suatu Analisis Berdasarkan qur’anic theory building) - Hafasnuddin Hafasnuddin (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIES Banda Aceh, 2014)
The purpose of this study is to descibe that the verses of Koran (Al Qur’an) can be used as a source grand, middle and applied theory in building marketing theory by deducting or inducting method. The Surah Al Mujadilah verses 11 from the holy Qur’an explains that Allah will increase the status of Moslem. Historically, from the VII to the XIV century the Moslem have high economic and business status, it means that the verse 11 of Al Mujadilah is significant in reality. So, we can use it as a source of marketing theory in qur’anic theory building. But, now a lot of Moslem have low business competence, it means that the verse 11 of Al Mujadilah is Not sifnificant in reality anymore. Although it is Not significant, we can still use the verse 11 of Al Mujadilah as source of theory in qur’anic theory building by describing the cause of why it is not significant anymore.